Efektivitas Rendam.Kaki dengan Air Hangat dan Pijat Kaki terhadap Penurunan Tekanan Darah pada Ibu Hamil dengan Hipertensi: The.Effectiveness of Feet Soak With.Warm Water and Feet Massage on Blood Pressure Reduction in Pregnant.Women with hypertension - Ika Warisantika; Yuni Kusmiyati; Sunartono Sunartono (Journal of Health, 2024)
Preeclampsia in Indonesia is around 3.8-8.5%, being the cause of high maternal mortality by 24%. (Depkes RI, 2015). Karawang District Health Office reports 31.1% of maternal deaths in this district are due to preeclampsia. This study aims to prove that foot both with warm water and foot massage are effective in reducing blood pressure in preeclampsia mothers. The study design used RCT. The research sample was 40 people divided into 4 groups: 10 people for foot soak intervention, 10 people for massage intervention, 10 people for foot bath and foot massage and 10 people in the control group. It was proven that the three interventions were effective in reducing hypertension in preeclampsia mothers, the highest average decrease in systolic 12.2 mmHg on the combined intervention, p-value 0.005, the lowest 8.2mmhg on foot massage intervention p-value 0.004, on the foot both group and massage group a p-value of 0.004. On day 5 of the foot both intervention a p-value of 0.005. The highest mean diastolic decrease was 8mmhg in the combined intervention a p-value of 0.005. The lowest decrease was 2.8mmhg on foot soak with warm water a p-value of 0.011. The statistical test results of the average decrease in blood pressure were all significant (p<0.05). The combined intervention of soaking and foot massage proved to be more effective than the intervention of soaking foot or foot massage.